(untitled) (The Review of Diabetic Studies, 2025)
Acute emergency situations expose field crews to intense psychological stress that can significantly affect cognitive processing, procedural accuracy, and overall response effectiveness. This review explores the psychological mechanisms linking acute stress with on-field performance among emergency personnel, including paramedics, firefighters, and first responders. It synthesizes evidence from experimental, clinical, and operational studies published between 2016 and 2025, focusing on how stress influences decision-making speed, attention, situational awareness, and the likelihood of procedural errors. Findings highlight that moderate stress can sometimes enhance performance through heightened arousal and focus, whereas excessive stress impairs working memory, motor precision, and judgment under pressure. Factors such as experience, resilience training, and team communication act as mediators of these effects. The review concludes by proposing a conceptual framework illustrating how psychological stress interacts with individual and organizational variables to shape field outcomes. Recommendations include integrating stress inoculation training, cognitive-behavioral coping strategies, and simulation-based learning to mitigate adverse stress effects. Understanding the mind’s role in acute performance is essential for advancing crew reliability and patient safety in critical emergency environments.